Growing Degree Day Climatology in Aydın, Türkiye - Ercan Yeşilırmak (Turkish Journal of Agriculture: Food Science and Technology)
Plants need to accumalate heat to complete a particular or whole growth period. This accumalation depends on temperature thresholds above or below which plant growth ceases, and on air temperature. It can be speculated that more heat accumulation is available for plants due to rapid warming within three or four decades. This study presents more recent heat accumulation for plants, quantified using a useful index called growing degree day (GDD), for five locations (Söke, Kuşadası, Aydın, Sultanhisar and Nazilli) in Aydın, Türkiye, during the latest climatic normal period from 1991 to 2020. GDD values were calculated both in monthly basis from March through October, and in daily basis from March 1st to October 31st. Monthly GDD averages, as expected, showed a pattern that increased from March to July or August, then decreased thereafter till October. Range and standart deviation showed approximately an opposite pattern, suggesting higher uncertainity in relatively colder months. The results are expected to provide farmers or agricultural practitioners with the latest averages of GDD to predict plant growth and development.